Путешествие Гулливера - Свифт Джонатан (Внеклассное чтение, 2016)
Экземпляры: Ф20 (20190306) / Инвентарный номер: 57371 / Цена: 80.00 / Сис.шифр: И(англ)ср / Авт.знак: С 24 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)